Mengembangkan Kreativitas Siswa Sekolah Menengah Kejuruan dalam Aktivitas Pembelajaran: Sebuah Scoping Review - Noor Daimah; Abdul Muhid (Universitas Muhammadiyah Metro, 2026)
Creativity is a crucial competence in vocational education as the workplace increasingly requires adaptive and innovative graduates from Vocational High Schools (SMK). Project-Based Learning (PjBL) has been widely recognized as a relevant instructional approach for fostering creativity through contextual and authentic projects, although research findings on its role in SMK remain fragmented. This article aims to systematically map existing studies on the role of PjBL in developing students’ creativity in vocational high schools using a scoping review approach. The review followed the Arksey and O’Malley framework and PRISMA-ScR guidelines, with literature searches conducted in Google Scholar, DOAJ, ResearchGate, and SINTA databases covering publications from 2015 to 2025. The results indicate that PjBL consistently contributes positively to students’ creativity, including creative thinking, problem-solving skills, collaboration, and the production of innovative products aligned with vocational fields. The effectiveness of PjBL implementation is influenced by contextual project design, teachers’ facilitative roles, availability of learning resources, and systemic school support. These findings highlight PjBL as a pedagogical approach that is highly relevant for fostering creativity in vocational education.